Genetic diversity analysis based on morphological traits and microsatellite markers in barley (Hordeum vulgare) - YADAV, SUNIL KUMAR; SINGH, ASHOK KUMAR; MALIK, REKHA (The Indian Journal of Agricultural Sciences, 2015)
The experimental material consisting of 10 barley (Hordeum vulgare L.) cultivars were evaluated using biometrical technique and microsatellite markers. A set 19 morphological and 47 SSR markers revealed significant differences among the quantitative and qualitative traits. In total 166 alleles were scored from PCR based amplification profiles for selected genotypes. The number of alleles ranged from 2 to 7 with an average of 3.52 alleles per locus. The band fragment size varied from 100 bp to 400 bp with PIC values ranging from 0.286 (Bmac154) to 0.804 (KV1/KV2) with an average of 0.551. Genetic diversity was estimated using Euclidean2 distance and UPGMA methods. Euclidean clustering revealed four clusters and groups II, III and IV exhibited highest mean value for most of the traits. Genotypes JB 1, LAKHAN, KB 1201 and RD 2035 were identified as most suitable genotypes for hybrid performance for yield attributing characters like tillers/plant, grains/spike, 1 000 grain weight, grain weight/spike, grain size and days to maturity. This information would be use as selection parameters to plan crosses and maximize the use of genetic diversity and expression of heterosis in barley breeding program for yield improvement.